Network centrality and pension fund performance - Alberto G. Rossi; David Blake; Allan Timmermann; Ian Tonks; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2015)
We analyze the relation between the location of a pension fund in its network and the investment performance, risk taking, and flows of the fund. Our approach analyzes the centrality of the fund's management company by examining the number of connections it has with other management companies through their commonality in managing for the same fund sponsors or through the same fund consultants. Network centrality is found to be positively associated with risk-adjusted return performance and growth in assets under management, after controlling for size and past performance, for domestic asset classes; however, we do not find this relation for foreign equity holdings. These findings indicate that local information advantages, which are much stronger among managers holding locally based stocks, exhibit positive externalities among connected managers. Of particular note is that we do not find that the centrality of a manager within one asset class (e.g., domestic bonds) helps the performance of the manager in another asset class (e.g., domestic equity), further indicating that our network analysis uncovers information diffusion effects. Network connections established through consultants are found to be particularly significant in explaining performance and fund flows, consistent with consultants acting as an important information conduit through which managers learn about each other's actions. Moreover, the importance of network centrality is strongest for larger funds, controlling for any economic scale effects. Better connected funds are also better able to attract higher net inflows for a given level of past return performance. Finally, more centrally placed fund managers are less likely to be fired after spells of low performance. Our results indicate that networks in asset management are one key source of the dissemination of private information about security values.
Keywords: 330